Usefulness of High-Frequency Ultrasonography in the Diagnosis of Melanoma: Mini Review - Belfiore, Maria Paola; Reginelli, Alfonso; Russo, Anna; Russo, Gaetano Maria; Rocco, Maria Paola; Moscarella, Elvira; Ferrante, Marilina; Sica, Antonello; Grassi, Roberto; Cappabianca, Salvatore (Frontiers in Oncology, 2021)
High frequency equipment is characterized by ultrasound probes with frequencies of over 10 MHz. At higher frequencies, the wavelength decreases, which determines a lower penetration of the ultrasound beam so as to offer a better evaluation of the surface structures. This explains the growing interest in ultrasound in dermatology. This review examines the state of the art of High frequency Ultrasound (HFUS) in the assessment of skin cancer to ensure the high clinical approach and provide the best standard of evidence on which to base clinical and policy decisions.(1)